Role of knowledge management in coastal tourism towards sustainable development goals in Sabah, Malaysia - Faizan Hasan Mustafa; Awangku Hassanal Bahar Pengiran Bagul (2020)
Tourism has emerged as a major sector of global economy, generating 319 million jobs and 10.4 % of GDP, and supporting merchandize exports worth US$1.7 trillion. These facts and figures justify a focused attention on tourism development under the United Nations Sustainable Development Goals (SDGs) for realizing its full economic potential. Malaysia has pledged to implement the SDGs for the socioeconomic benefits. Policies are being laid down for promoting sustainable tourism. With a vast coastline and rich natural resources, Malaysia offers opportunities for achieving the targets of SDG14. A knowledgebased development of this tourism sub-sector will help the coastal communities and contribute to national economy. The existing infrastructure and trained human resources can aid in transformation of tourism with more sustainable practices. Such practices will generate income and dissuade the coastal communities from unsustainable exploitation of marine environmental resources in favor of higher income that sustainable tourism will generate. This paper is based on a general survey of the status of nature-based tourism in coastal areas of Sabah. Observations were focused on existing infrastructure in tourism hotspots, trend of exploitation of natural resources and feedback from tourists. The work also involved review of documents related to SDG targets for making progress in implementation. This paper discusses ways and means of promoting nature-based tourism through knowledge-based plans and strategies. These include follow-up action on: regulating the tourism according to carrying capacity of tourism hotspots, diversification of tourism sub-sectors, linking socio-economic benefits with environmental conservation, academia-industry cooperation, academia-community interaction, and application of knowledge management tools to properly shape development of nature tourism in coastal areas. The role of institutions of higher education in addressing the challenges in developing sustainable tourism, adapting the DPSIR framework to local conditions and constructing models of tourism compatible with the SDGs have been highlighted in this paper.